Taking Flight : The Nadine Ramsey Story - Ramsey, Raquel; Aurand, Tricia (Book collections on Project MUSE., 2020)
"This is the first biography of Nadine Ramsey, a stunt and racing pilot who served as one of 1,102 Women's Air Force Service Pilots (WASP) during World War II. The WASP flew domestic flights for the military, freeing up male pilots to enter the European and Pacific theatres of war. Nadine was one of only 303 women who ferried military aircraft. She was also the first Kansas woman to obtain a Civil Aeronautics Authority private flying license, and the first woman pilot to own her own fighter plane. The manuscript follows Nadine from her family's rural Illinois roots to Wichita, where she grew up and began her flying career. Flight would take Nadine to California, where she joined the Civil Air Patrol and later the WASP. After the war, while she retained her ties to aviation, earlier injuries prematurely forced her to stop flying, and she passed away before the federal government fully recognized the WASP's service. Nadine's story is exceptional, but it also reveals intimate details of women's early service in the military, and the trauma and lack of recognition faced by female veterans"--